Analysis of Pancawati Batik Marketing Communication Strategy in Building Brand Awareness Through Instagram" (Study in Cibuluh Batik Village, Bogor) - Shoffi Nurfitriati; Budi Santoso (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to analyze the marketing communication strategy of Batik Pancawati in building brand awareness through Instagram as a digital medium. The background of this research highlights the importance of digital marketing for batik SMEs in the global era, particularly to strengthen the existence of Batik Pancawati as the pioneer of Kampung Batik Cibuluh, Bogor. This research employs a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The findings indicate that Batik Pancawati applies an Integrated Marketing Communication (IMC) strategy by utilizing educational content, digital promotions, community engagement, and audience interaction through Instagram features (Feeds, Reels, Stories, Hashtags). The strategy has proven effective in raising brand awareness, although challenges remain in terms of limited resources and consistency in managing social media. The study concludes that optimizing Instagram use can strengthen brand awareness while supporting local cultural preservation through digital marketing.